GROWTH AND SURVIVAL RATE OF VANAME SHRIMP (Litopenaeus vannamei) PL-10 ON DIFFERENT STOCKING DENSITY - Pratiwi Pratiwi; Muhammad Marzuki; Bagus Dwi Hari Setyono (AQUASAINS, 2021)
Litopenaeus vannamei is a commercial shrimp that has high economic value. In recent years, the main commodity contributing to the aquaculture sector in Indonesia is vaname shrimp. Vaname shrimp cultivation aims to meet the increasing market demand. One of the factors that influence the success of vaname shrimp cultivation is the stocking density. This study aims to determine the growth and viability of PL-10 vaname shrimp (Litopenaeus vannamei) fry at different stocking densities. This study used a completely randomized design (CRD). There were 4 treatments, namely P1 with a stocking density of 75 heads / 40 liters, P2 with a stocking density of 150 heads / 40 liters, P3 with a stocking density of 225 heads / 40 liters, and P4 with a stocking density of 300 heads / 40 liters, respectively. 4 repetitions. The research data were analyzed using statistical analysis Univariate One Way Analysis of Variance at 5% level with a 95% confidence interval. The results showed that the highest daily growth rate was obtained in treatment P1 with an average value of 26.836 ± 0.745% / day, the highest daily length growth rate was obtained in treatment P1 with an average value of 6.719 ± 0.103% / day, the highest absolute weight growth was obtained at treatment P1. P1 treatment with an average value of 0.031 ± 0.027 gram, absolute length growth was obtained in treatment P1 with an average value of 23.025 ± 0.667 mm, the highest survival rate was obtained in treatment P2 with an average value of 96.333 ± 3.549%, but not different real with treatment P2 (93.333 ± 3.443%) and treatment P4 (92.417 ± 2.062). The conclusion of this study is that stocking density has a significant effect on the growth of vannamei shrimp which are being maintained at the PL-10 stage. The best stocking density in this study was P1 treatment (75 fish / 40 liters).